2020
DOI: 10.1371/journal.pntd.0008508
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma haematobium infection and environmental factors in Southwestern Tanzania: A cross-sectional, population-based study

Abstract: Schistosomiasis is a leading cause of morbidity in Africa. Understanding the disease ecology and environmental factors that influence its distribution is important to guide control efforts. Geographic information systems have increasingly been used in the field of schistosomiasis environmental epidemiology. This study reports prevalences of Schistosoma haematobium infection and uses remotely sensed and questionnaire data from over 17000 participants to identify environmental and socio-demographic factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 76 publications
(125 reference statements)
1
12
2
Order By: Relevance
“… 27 The frequency and type of water contact also depend on water sources and its availability in the community. 28 …”
Section: Discussionmentioning
confidence: 99%
“… 27 The frequency and type of water contact also depend on water sources and its availability in the community. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Like other neglected tropical diseases (NTDs), schistosomiasis is influenced by various environmental factors that govern the persistence of the disease and the survival of snail vectors [53][54][55][56]. To characterize the present climatic conditions, bioclimatic variables were obtained from the WorldClim dataset (1970-2000) (v2.1) (https://worldclim.org/) (access date: 2 November 2021) [57] at the 1-km resolution (30-arc seconds).…”
Section: Environmental Variablesmentioning
confidence: 99%
“…27 The frequency and type of water contact also depend on water sources and its availability in the community. 28 There was no significant association between proximity likely not to use protective gears while at their working sites. Our study is similar to a study by 19 which revealed that those educated had significantly better knowledge on the signs and symptoms, transmission (snail) and prevention of schistosomiasis when compared to their counterparts.…”
Section: Discussionmentioning
confidence: 90%